The Influence of Motivation and Responsible Leadership on Task Performance with Employee Well-Being as a Mediating Variable - Ade Putra Priadi; Padmantyo, Sri (Majapahit Journal of Islamic Finance and Management, 2025)
This research investigates the effects of motivation and responsible leadership on task performance, with employee well-being acting as a mediating factor among staff members at Maguan Husada Hospital. In the fast-paced and demanding setting of the healthcare industry, it is crucial to identify internal organizational elements that influence employee productivity. Motivation and responsible leadership are recognized as essential drivers that can enhance employee well-being, which subsequently impacts their task performance. In this context, well-being is analyzed as an intermediary variable that connects motivation and responsible leadership to task-related outcomes. A quantitative research design was adopted, utilizing a survey method. A purposive sampling technique was applied to select 150 active staff members at Maguan Husada Hospital. Data were obtained through a structured questionnaire and analyzed using SmartPLS. The analysis confirmed that all proposed hypotheses—namely, the impact of motivation on well-being, the influence of responsible leadership on well-being, the direct effects of both motivation and responsible leadership on task performance, as well as the mediating function of well-being are statistically significant. The findings provide both theoretical insights for the body of knowledge in human resource management within the healthcare sector and practical guidance for hospital administrators seeking to enhance staff performance through improved motivation, responsible leadership practices, and a stronger focus on employee well-being.